The role of physical therapy in the recovery of the patient with pectus carinatum - Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2022)
I chose this theme from the desire to know the different means of recovery through physical therapy of pectus carinatum, since there are quite a few who suffer from this condition. The patient being a child, the desire to recover it was amplified, starting to "the road", with a lot of optimism and perseverance. It turned out to be a great challenge for me, as I realized how much patience you need to have, but especially to be in control of the situation, in order to motivate him to complete his tasks. The main purpose of the study is to demonstrate the effectiveness of kinetotherapeutic means in pectus carinatum and improve the quality of life of the subject undergoing therapy. Through the implemented program, it is aimed at toning the abdominal muscles, paravertebral muscles and respiratory muscles.